Copper light-catching electrodes for organic photovoltaics. Issue 4 (5th April 2017) - Pereira, H. Jessica; Hutter, Oliver S.; Dabera, G. Dinesha M. R.; Rochford, Luke A.; Hatton, Ross. A.
Abstract : Plasmon-active optically thin copper films catch red light and transfer the energy to the photoactive layer in organic photovoltaic devices. Abstract : Optically thin copper films with a random array of sub-optical wavelength apertures couple strongly with light in the wavelength range 600–800 nm due to excitation of surface plasmonic resonances. Herein we show that this trapped light can be used to excite electronic transitions in a nearby strongly absorbing organic semiconductor before the plasmonic excitations dissipate their energy as heat into the metal. This energy transfer process is demonstrated using model small molecule and polymer photovoltaic devices (based on chloro-aluminium phthalocyanine:C60 and PCE-10:PC70 BM heterojunctions respectively) in conjunction with a nano-hole copper electrode formed by thermal annealing an optically thin Cu film supported on polyethylene terephthalate. The efficiency of this process is shown to be highest for wavelengths in the range 650–750 nm, which is part of the solar spectrum that is weakly absorbed by today's high performance organic photovoltaic devices, and so these findings demonstrate that this type of electrode could prove useful as a low cost light catching element in high performance organic photovoltaics.